Preparation and characterization of bioactive chitosan-based films incorporated with olive leaves extract for food packaging applications - Musella, Enrica (2021)
Chitosan films with olive leaf extract (OLE) incorporated at different concentrations were characterized regarding their antimicrobial, antioxidant and some relevant physical properties (i.e., solubility, water vapor permeability, and tensile properties). Results indicate that the active films have substantial antimicrobial activity against Listeria monocytogenes and Campylobacter jejuni mostly extending the microorganisms lag phase. A lower level of inhibition was found in the case of Escherichia coli. However, the OLE seems not to improve the intrinsic antimicrobial properties of the chitosan itself, except for C. jejuni. These results were confirmed with in situ testing using chicken. The chitosan films with OLE exhibited antioxidant activity, increasing with the OLE concentration, from 0.04 to 0.15 g/L ascorbic acid equivalents, corresponding to films with 10%–30% OLE relative to the chitosan. Chitosan films loaded with OLE exhibited a higher solubility in food simulants and a reduced permeability against water vapor. Overall, the combination of OLE and chitosan allows to obtain a promising active bio-based packaging solution for addressing safety and quality issues.